(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The current study aims to apply the methods of evaluating investment decisions to extract the highest value and reduce the economic and environmental costs of the health sector according to the strategy.In order to achieve the objectives of the study, the researcher relied on the deductive approach in the theoretical aspect by collecting sources and previous studies. He also used the applied practical approach, relying on the data and reports of Amir almuminin Hospital for the period (2017-2031) for the purpose of evaluating investment decisions in the hospital. A set of conclusions, the most important of which is: The failure to apply some methods of evaluating investment projects such as the inverse payback period, the internal rate of return, or the net present value may be due to the lack of sufficient accounting background among those in charge of the financial and accounting departments, which makes them unable to apply such methods in evaluating Investment projects, and it was found that the research sample hospital achieves economic profitability in accordance with the economic evaluation criteria, and therefore the project appears to be feasible and acceptable from an economic point of view, which indicates the success of the project. The research concluded with a set of recommendations, the most important of which are: Work periodically in the research sample hospital in the evaluation process and use the same indicators in addition to indicators of performance efficiency after implementing the project in order to identify the weaknesses and strengths of the project in order to avoid mistakes from the beginning and develop future plans for the continuation of the productive process